DIFFICULTIES OF READING ARABIC AS A FOREIGN LANGUAGE - Shaban, Ali (Journal of Oriental Studies, 2023)
This paper aims to investigate the problems associated with reading Arabic as a foreign language. Workers in the field of teaching Arabic as a foreign language must have noticed that learners of Arabic face some problems that lead to hindering or slowing down their progress in reading as a language skill. This paper tried to pinpoint the difficulties that face non-native Arabic learners, and the different factors pertaining to those problems. An empirical tool, to be described below, was used to achieve the objectives of this paper. Despite the fact that a lot of work has been done in this area of study, the overwhelming majority of the findings of this paper was not shown or mentioned in earlier works. The scope of this study covered the orthographic, phonological, lexical, syntactic, semantic, and contextual factors that shaped the accuracy, fluency of reading, and comprehension of the texts read by the students participated in this study. The results showed that some areas in the Arabic language posed a real challenge to the reader; (1) Predicting the vowels that shape the phonological structure of the word. (2) Determining the correct vowel that goes with the second consonants of the verb-root. (3) Determining the correct vowel that goes with the tense-subject morpheme of the present tense. (4) The grammatical case endings of verbs and nouns according to the grammatical function they carry in the sentence. Key words: Arabic as a Foreign Language, Arabic writing system, Accuracy in reading Arabic. Fluency in Reading Arabic, Vowel Marking in Arabic.